Suzuki cross-coupling and intramolecular aza-michael addition reaction sequence towards the synthesis of 1,10b-epi-7-deoxypancratistatins and their cytotoxicity studies - Pandey, Ganesh; Balakrishnan, Madhesan; Swaroop, Pandrangi Siva (European Journal of Organic Chemistry, 2008)
The development of an efficient approach to the construction of a phenanthridone is described. The convergent strategy commences with the preparation of Suzuki cross-coupling reaction precursors, arylboronic acid 12 and a-iodo enone 14, from piperonylamine (9) and (-)-D-quinic acid (10), respectively. The coupling of 12 and 19 followed by a key intramolecular aza-Michael addition produced phenanthridone 21 featuring a cis-fused B-C ring junction. The syntheses of compounds 25 and 26, both of which are C-1 and C-10b epimers of the naturally occurring potent antitumor agent 7-deoxypancratistatin (2), from 21 are elaborated in detail in this paper. The cytotoxicities of 25 and 26 were evaluated against three different cancer cell lines. Compound 26 served as a moderate growth inhibitor of THP-1 monocytic cells (GI(50) = 14.5 mu g/mL). ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: antitumor agents; Chiral pool; Cross-coupling; Intramolecular aza-Michael addition; Pancratistatin

Suzuki cross-coupling/reductive debenzyloxycarbonylation sequence for the syntheses of [c]annulated isoquinolines: application for the syntheses of pancratistatin-like isoquinolines - Pandey, Ganesh; Balakrishnan, Madhesan (Journal of Organic Chemistry, 2008)
A two-step strategy involving Suzuki cross-coupling of boronic acids with a diverse array of alpha-iodoenones followed by hydrogenation is developed for the construction of [c]annulated isoquinolines. This mild and efficient procedure is also applied to the synthesis of highly oxygenated isoquinolines.